Analgesic effect of ropivacaine combined with dexmedetomidine in the postoperative period in children undergoing ultrasound-guided single-shot sacral epidural block: A systematic review and meta-analysis - Quan, Shoubo; Lu, Yuexia; Huang, Yujie (Frontiers in Pediatrics, 2023)
Objective: This study aims to evaluate the efficacy of dexmedetomidine as an adjuvant to ropivacaine in prolonging postoperative analgesia and reducing pain scores in children undergoing surgery. Methods: Five online databases were searched for RCTs on postoperative analgesia of pediatric patients undergoing ultrasound-guided single-shot sacral epidural block with dexmedetomidine as an adjuvant to ropivacaine up to January 2, 2023. Pain score and sedation score at 2, 4, 8, 12, and 24 hours after the operation, the time of first receiving additional analgesic drugs, and the number of postoperative adverse effects were selected to compare the efficacy and safety of combined treatment with ropivacaine alone for pediatrics. The standard mean difference (SMD) or odds ratio (OR) and the corresponding 95% confidence interval (95%CI) were calculated by using a random-effects model. Results: A total of 295 articles were retrieved, but only 20 records were included in this meta-analysis. The results showed that dexmedetomidine combined with ropivacaine for sacral epidural block in children undergoing ultrasound-guided single-shot sacral epidural block had a more prolonged analgesia effect (SMD = 3.47, 95%CI: 2.80, 4.14). There were lower analgesia scores at 2h(T1), 4h(T2), 8h(T3), 12h(T4), and 24h(T5) in postoperative period (T1: SMD = -1.02, 95%CI: -1.31, -0.72; T2: SMD = -1.02, 95%CI: -1.32, -0.72; T3: SMD = -0.84, 95%CI: -1.12, -0.56; T4: SMD = -0.61, 95%CI: -1.03, -0.20; T5: SMD = -1.03, 95%CI: -1.28, -0.78). And the incidence of adverse effects was similar between the two groups (OR = 0.84, 95%CI: 0.59, 1.18). Conclusions: The results of this review and meta-analysis support that dexmedetomidine, as an adjuvant to ropivacaine, can improve postoperative analgesia of surgery and significantly prolong the analgesic time in children, with a similar incidence rate of adverse symptoms when compared with ropivacaine alone.